2017
DOI: 10.1093/pubmed/fdx140
|View full text |Cite
|
Sign up to set email alerts
|

Association between self-rated health and ideal cardiovascular health: The Baptist Health South Florida Employee Study

Abstract: Favorable SRH was consistently associated with better CVH.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 11 publications
(19 citation statements)
references
References 40 publications
1
18
0
Order By: Relevance
“…The findings of this study are comparable with those of other studies that have explored a similar association . However, unlike our study, most of these studies (with 1 exception) were conducted among populations of narrow sociodemographics that limit the generalizability of their findings.…”
Section: Discussionsupporting
confidence: 85%
See 4 more Smart Citations
“…The findings of this study are comparable with those of other studies that have explored a similar association . However, unlike our study, most of these studies (with 1 exception) were conducted among populations of narrow sociodemographics that limit the generalizability of their findings.…”
Section: Discussionsupporting
confidence: 85%
“…The findings of this study are comparable with those of other studies that have explored a similar association. [20][21][22] However, unlike our study, most of these studies (with 1 exception 20 ) were conducted among populations of narrow sociodemographics that limit the generalizability of their findings. In a cross-sectional analysis of 10 687 men and women aged 45 to 64 years free of CVD in the Polish-Norwegian Study, 21 researchers demonstrated that mean number of ideal metrics and total CVH score increased with increasing SRH, measured on a scale of 1 to 10.…”
Section: Comparison To Previous Studiesmentioning
confidence: 81%
See 3 more Smart Citations